2020
DOI: 10.3389/fmicb.2020.00580
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Escherichia coli in Dogs Reveals the Predominance of ST372 and the Human-Associated ST73 Extra-Intestinal Lineages

Abstract: Escherichia coli is a ubiquitous commensal and pathogen that has also been recognized as a multi-sectoral indicator of antimicrobial resistance (AMR). Given that latter focus, such as on resistances to extended-spectrum cephalosporins (ESC) and carbapenems, the reported population structure of E. coli is generally biased toward resistant isolates, with sequence type (ST)131 being widely reported in humans, and ST410 and ST648 being reported in animals. In this study, we characterized 618 non-duplicate E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
39
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 53 publications
12
39
4
Order By: Relevance
“…A French study also reached a similar conclusion, identifying ST372 as the major pathogenic E. coli ST in dogs (42). Similar findings in two distinct geographic areas may indicate a dog-specific distribution of pathogenic E. coli clones instead of the effect of regional factors (42). In contrast to LeCuyer's and Valat's reports, ST372 was observed only once in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A French study also reached a similar conclusion, identifying ST372 as the major pathogenic E. coli ST in dogs (42). Similar findings in two distinct geographic areas may indicate a dog-specific distribution of pathogenic E. coli clones instead of the effect of regional factors (42). In contrast to LeCuyer's and Valat's reports, ST372 was observed only once in our study.…”
Section: Discussionsupporting
confidence: 89%
“…They therefore concluded that each host species may have a particular ST that comprises most of the E. coli uropathogens. A French study also reached a similar conclusion, identifying ST372 as the major pathogenic E. coli ST in dogs (42). Similar findings in two distinct geographic areas may indicate a dog-specific distribution of pathogenic E. coli clones instead of the effect of regional factors (42).…”
Section: Discussionmentioning
confidence: 59%
“…The prevalence of APEC-associated variants, used in the RF model, was investigated in isolates sampled from other host niches. Specifically, we analysed the E. coli reference collection (ECOR) 42 , 175 human ExPEC strains 28 , 14 disease-associated strains from dogs 51 and 521 strains from healthy cattle 52 . The APEC-associated genetic variants also occurred in humans and other animals implying that host species does not constitute a complete gene-pool barrier between the niches.…”
Section: Resultsmentioning
confidence: 99%
“…45 Among the MLST genotypes reported in this study, some of them have been isolated in both humans and animals; in particular, ST372, ST410, and ST224 have been reported previously in humans and pets. 48,49 This shows that these, and probably many other E. coli genotypes carrying antimicrobial resistance genes, can be shared between animals and humans.…”
Section: Discussionmentioning
confidence: 96%